Readiness for Change: The Secret to Managing Employee Performance - Novitasari, Dewiana (International Journal of Social and Management Studies, 2021)
This study aimed to measure the effect of transformational leadership on employee performance of the employee of a fashion industry in West Java which is mediated by readiness for change. Sample data collected from 130 employees by simple random sampling technique. Data processing was used in the SEM method. The results of this study concluded that transformational leadership has a negative and significant effect on employee performance, but transformational leadership has a positive and significant effect on readiness for change. This study conclude also that readiness for change has a positive and significant effect on the relationship between transformational leadership and employee performance. Readiness for change as partial mediator. This new research proposed a model for building employee performance among the employee of a fashion industry in West Java through enhancing transformational leadership practice with readiness for change as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.